Association between serum cholinesterase levels and body composition in vegetable farmers assessed by bioelectrical impedance analysis - Bibit Nasrokhatun Diniah; Sulistiyani Sulistiyani; Tri Joko; Budiyono Budiyono (AcTion: Aceh Nutrition Journal, 2025)
Exposure to all pesticide classes can have a disruptive effect on metabolism and energy storage. The bioindicator that can be used to identify farmers exposed to pesticides is acetylcholinesterase (AChE). AChE can be a good indicator for changes in body composition due to its associations with various metabolic and physiological parameters. Abnormal AChE levels stimulate nicotinic and muscarinic receptors in various organs, causing a wide range of metabolic disorders, including changes in the body composition. This study aimed to examine the correlation between long-term pesticide exposure and potential alterations in body composition. This research was conducted in Sagarahiang village, one of the highest vegetable producers in Kuningan, West Java onJuly-August 2024. And it was a cross-sectional study of 46 farmers who sprayed pesticides in vegetable areas and was determined by purposive sampling. Data collected through interview using questionnaires and some tools, like indicators of pesticide exposure were measured by cholinesterase serum and history of exposure, whereas parameters of body composition were measured by bioelectrical impedance analysis (BIA) using a body fat monitor with eight electrodes. Data analysis using the Pearson correlation test. The percentage of subjects with abnormal AChE activity was four persons (8,9%). AChE levels had no correlation with all components of the exposure history, but had a significant correlation with body composition parameters (p<0,05), body weight (p=0,027), Body Mass Index (BMI) (p=0,020), total fat (p=0,038), visceral fat (p=0,030), and resting metabolism (p=0,037) with a weak correlation (R 0,31-0,34). Based on this study, AChE is not strong enough to assess changes in body composition clinically.